Bio-Psychosocial Health Disorder - Migraine with Multidimensional Approach (Homoeopathy for All, 2024)
Migraine is one of the most  common neurological disorders. It  is classified as a primary headache  disorder characterized by recurrent  headaches, typically unilateral which  lasts for 4-72 hours, associated  with of nausea, vomiting and  photophobia. The word Migraine  is a corrupted form of the word  ‘hemicrania’, which meant one sided  headaches. Therefore it is usually  thought of as one sided headaches.  This article provides an overview  of the aetiology, diagnosis, and  appropriate general & homoeopathic  management of this disorder.
Keywords: Avena sativa; Chionanthus; Gelsemium